2013
DOI: 10.1099/jmm.0.059915-0
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of VIM-4 and NDM-1 metallo-β-lactamase among carbapenem-resistant Enterobacteriaceae

Abstract: The purpose of this study was to identify the mechanisms leading to carbapenem resistance among multidrug-resistant Enterobacteriaceae isolates recovered from hospitalized patients with nosocomial infections in Mubarak Al Kabeer Hospital, Kuwait. Fourteen carbapenem-resistant Enterobacteriaceae isolates were obtained from inpatients in different wards and intensive care units between April 2009 and February 2011. Antibiotic susceptibilities were determined using the E-test method. Genes encoding b-lactamases w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
59
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(64 citation statements)
references
References 32 publications
5
59
0
Order By: Relevance
“…No isolate was found to produce the KPC, VIM, or IMP betalactamase, although these carbapenemases have been previously detected in Saudi Arabia and Kuwait (2,(22)(23)(24). For 17 isolates, no carbapenemase activity or carbapenemase genes were identified, suggesting a noncarbapenemase-related resistance mechanism.…”
Section: Discussionmentioning
confidence: 81%
“…No isolate was found to produce the KPC, VIM, or IMP betalactamase, although these carbapenemases have been previously detected in Saudi Arabia and Kuwait (2,(22)(23)(24). For 17 isolates, no carbapenemase activity or carbapenemase genes were identified, suggesting a noncarbapenemase-related resistance mechanism.…”
Section: Discussionmentioning
confidence: 81%
“…Lascols et al and Castanheira et al also reported carriage of bla NDM-1 among E. cloacae [33, 34]. Emergence of bla NDM-1 producing E. cloacae clinical isolates was reported from Singapore [35], China [36], Australia [37], United States [38], Kuwait [39], Turkey [40], and Canada [41]. MBLs other than NDM-1 also have been reported by various authors in E. cloacae : bla IMP-1 from Turkey [42], bla IMP-8 from Taiwan [43], bla VIM1-4 from Italy [4446], bla VIM-2 from Korea [47], and bla VIM-12 from Greece [48].…”
Section: Resultsmentioning
confidence: 99%
“…Both the 915 and 917 isolates were identified as Salmonella enterica serotype Kentucky (antigens 8,20:i,z 6 ) in an agglutination test according to the Kauffmann-White scheme by using commercial antisera (Murex, Dartford, the United Kingdom; Statens Serum Institut, Copenhagen, Denmark; and Denka Seiken, Tokyo, Japan). The clonal relationship between the two isolates was evaluated by pulsed-field gel electrophoresis (PFGE) using restriction enzyme XbaI as described previously (1). The two isolates appeared very similar ( Fig.…”
mentioning
confidence: 99%